The Random Walk Theory: An Empirical Test in the Nigerian Capital Market - Michael, NWIDOBIE Barine (Asian Economic and Financial Review, 2014)
The movement of stock prices has been found to be random in some capital markets across the world and in others non-random. Analysis of all-price-index (API) data of shares of listed firms on the Nigerian Stock Exchange from January 2000 to December 2012 using the Augmented Dickey-Fuller (ADF) test shows that share price movements on the Nigerian Stock Exchange do not follow the random walk pattern described by Fama (1965), and thus the random walk hypothesis is not supported by findings in the Nigerian capital market. Results also indicate the existence of market inefficiencies in the Nigerian capital market necessitating the inflow of cheap and free information about security fundamentals into the market for share pricing by the forces of demand and supply.